THE NYAYA -VAISESIKAS AS INTRPRETERS OF SRUTI - George Chemparathy (Journal of Dharma, 1978)
We know from Yaska’s Nirukta that already during his time, which is said to be not later than 500 B.C., there were dIfferent schools of Vedic interpretation. Yaska mentions no less than eight schools. The more important among these seem to have been the school of the Airihasikas and that of the Nirukas,Yaska himself being a follower of this latter school. The Nairuktas on the other hand, were etymologists and tried to show that the events mentioned in the Veda are not to be understood in a literal sense.